MOTIVATIONAL COMPONENT OF PEDAGOGICAL SKILLS’ DEVELOPMENT OF FUTURE TEACHERS OF LABOR EDUCATION AND TECHNOLOGIES - Kovalchuk, Vasyl; Androsenko, Artem; Sherudylo, Andrii; Velychko, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Relevance. The future teachers’ motivation problem and value orientations as basic characteristics of readiness for the pedagogical skills development is one of the key issues in the conditions of professional training in higher education institutions.Objective: The article's aim is to substantiate in a theoretical way and experimental investigation the reasons, to disclose the set of values orientation of future teachers of labour education and technologies as development factors of their pedagogical skills.Methods: theoretical: analysis of current psychological and pedagogical research on the development difficulties of pedagogical skills; generalization and systematization of approaches to the study of personal motivation and values; empiric: questionnaire according to the M. Rokych’s method "Value Orientations", correlation of ranking results with A. Maslow's pyramid of values and needs; methods of mathematical statistics.Results: Results: The essence of the "pedagogical skills" concept has been clarified. Based on the analysis of academic sources, the content of such categories as motives, motivation, values, and value orientations has been specified. The research method of the features of the motivational and value sphere for future teachers of labour education and technologies have been described. A qualitative and quantitative analysis of the distribution of value orientations of future teachers of labour education and technologies have been represented.Conclusions: Founded on the study results, the priority groups of motives and values that are leading for those seeking education at this day stage of social evolution are identified, that is safety and comfort, health, interesting work, freedom and independence, productive life, development, and communication.